A copper diimine‐based honeycomb‐like porous network as an efficient reduction catalyst - Ahmad, Abrar; Shah, Syed N. A.; Arshad, Mehwish; Bélanger‐Gariepy, Francine; Tiekink, Edward R. T. *; Rehman, Zia (John Wiley, 2021)
Nitrophenols are among the widely used industrial chemicals worldwide; however, their hazardous effects on environment are a major concern nowadays. Therefore, the conversion of environmentally detrimental p‐nitrophenol (PNP) to industrially valuable p‐aminophenol (PAP), a prototype reaction, is an important organic transformation reaction. However, the traditional conversion of PNP to PAP is an expensive and environmentally unfriendly process. Here, we report a honeycomb‐like porous network with zeolite‐like channels formed by the self‐organization of copper, 1,10‐phenanthroline, 4,4′‐bipyridine, and water. This porous network effectively catalyzed the transformation of hazardous PNP to pharmaceutically valued PAP. In the presence of complex, PNP to PAP conversion occurred in a few minutes, which is otherwise a very sluggish process. To assess the kinetics, the catalytic conversion of PNP to PAP was studied at five different temperatures. The linearity of lnCt/Co versus temperature plot indicated pseudo‐first‐order kinetics. The copper complex with zeolite like channels may find applications as a reduction catalyst both on laboratory and industrial scales and in green chemistry for the remediation of pollutants.